Silver and Gold Compounds as Antibiotics - Christina N. Banti; Sotiris K. Hadjikakou (Antibiotics)
This Special Issue entitled “Silver and Gold Compounds as Antibiotics” covers a selection of recent research and review articles focused on biological inorganic chemistry [...]